EVALUATION PARAMETERS FOR SPHERICAL AGGLOMERATES FORMED BY SPHERICAL CRYSTALLISATION TECHNIQUE. - PARIDA R (International Journal of Pharma and Bio Sciences, 2010)
Spherical crystallization is the novel agglomeration technique that can transform directly the fine crystals produced in the crystallization process into a spherical shape. It is the particle engineering technique by which crystallization and agglomeration can be carried out simultaneously in one step to transform crystals directly into compacted spherical form. This technique of particle design of drugs has emerged as one of the areas of active research currently of interest in pharmaceutical manufacturing and recently came into the forefront of interest or gained great attention and importance due to the fact that crystal habit can be modified during the crystallization process. In consequence of such modifications in the crystal habit certain micrometric properties and physicochemical properties can also be modified .As this technique forms the spherically agglomerated crystals showing significant effect on the formulation and manufacturing of pharmaceutical dosage form. Therefore it is necessary to evaluate and characterized these spherically agglomerated crystals by using the different parameters so as to differentiate it from the raw crystals.